2000
DOI: 10.1007/bf02682109
|View full text |Cite
|
Sign up to set email alerts
|

Role ofBcl-2, Bax, andBak in spontaneous apoptosis and proliferation in neuroendocrine lung tumors: Immunohistochemical study

Abstract: Fifty-six primary neuroendocrine lung tumors were examined morphologically and histologically and their apoptosis level was determined. Malignant carcinomas were characterized by increased apoptotic index and enhanced expression ofBcl-2, Bak, p53, and Ki-67 compared to typical carcinoid. However, apoptosis in these tumors was not completed. Proteins of the Bcl family play an important role in the regulation of spontaneous apoptosis in neuroendocrine lung tumors. Bcl-2 accumulating in the nucleus is a morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
1
8
0
1
Order By: Relevance
“…Increased expression of Bak might be enough to antagonize the antiapoptotic effect of anti-apoptosis Bcl-X L and upregulated Ser (112)-phosphor-Bad. It has been shown that Bak is the most important pro-apoptosis Bcl-2 family member, whose function is to determine whether or not apoptosis proceeds in the cell [26][27][28][29]. This observation correlates with the observation that Bid expression levels remained unaltered, while phospho-(Ser112)-Bad and Bak were upregulated in MDA-MB-231 breast carcinoma cells treated with LIGHT in the presence of IFNγ [19].…”
Section: Discussionsupporting
confidence: 54%
“…Increased expression of Bak might be enough to antagonize the antiapoptotic effect of anti-apoptosis Bcl-X L and upregulated Ser (112)-phosphor-Bad. It has been shown that Bak is the most important pro-apoptosis Bcl-2 family member, whose function is to determine whether or not apoptosis proceeds in the cell [26][27][28][29]. This observation correlates with the observation that Bid expression levels remained unaltered, while phospho-(Ser112)-Bad and Bak were upregulated in MDA-MB-231 breast carcinoma cells treated with LIGHT in the presence of IFNγ [19].…”
Section: Discussionsupporting
confidence: 54%
“…BCL-2 is overexpressed in 69-90% of SCLC tumors as well as in a majority of the currently available cell lines [11][12][13][14]. Furthermore, expression of BCL-2 is higher in metastatic tumors compared to localized disease [15,16]. Most importantly, increased BCL-2 expression confers chemoresistance in SCLC by inhibiting apoptosis [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Bcl-2 overexpression, mainly with nuclear localization, together with a high Bcl-2/Bax ratio, was correlated directly with an elevated spontaneous apoptosis index (31)(32)(33), and with the absence of metastasis in SCLC tumors (34). The relationship between Bcl-2 overexpression and tumor stage is less clear, but an inverse correlation between Bcl-2 levels and cancer progression has already been pointed out (29,(34)(35)(36). In addition, there are cases of reduced Bcl-2 levels upon in vitro acquisition of resistance to cisplatin (37).…”
Section: Discussionmentioning
confidence: 94%
“…It has been demonstrated that, regardless of the frequently observed Bcl-2 overexpression in SCLC cell lines (2) and tumors (3), there is no correlation between Bcl-2 expression and resistance to therapy and/or patient survival (26)(27)(28)(29)(30). In fact, Bcl-2 overexpression, mainly with nuclear localization, together with a high Bcl-2/Bax ratio, was correlated directly with an elevated spontaneous apoptosis index (31)(32)(33), and with the absence of metastasis in SCLC tumors (34). The relationship between Bcl-2 overexpression and tumor stage is less clear, but an inverse correlation between Bcl-2 levels and cancer progression has already been pointed out (29,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%